The Outbreaks of Acute Encephalitis Syndrome in Uttar Pradesh, India (1978–2020) and Its Effective Management: A Remarkable Public Health Success Story - Srivastava, Neha; Deval, Hirawati; Mittal, Mahima; Kant, Rajni; Bondre, Vijay P. (Frontiers in Public Health, 2022)
Introduction: Acute encephalitis syndrome (AES) is a major public health enigma in India and the world. Uttar Pradesh (UP) is witnessing recurrent and extensive seasonal AES outbreaks since 1978. These AES outbreaks in UP led Government of India and UP state government to respond effectively and devising various mitigation measures to reduce AES burden as well as to prevent AES associated mortality, morbidity and disability in Uttar Pradesh. Methods: This review utilized search engines such as PubMed, google scholar, Research Gate, Cochrane, Medline to retrieve articles and information using keywords “Acute Encephalitis Syndrome”, “Etiology of Acute encephalitis syndrome”, “control strategies for Acute encephalitis syndrome”, “Investigation of Acute encephalitis syndrome outbreaks”. Data were collected from progress reports of government schemes as well from websites of Indian Council of Medical Research (ICMR), National Vector Borne Disease Control Programme (NVBDCP) and Integrated Disease Surveillance Programmes (IDSP) to present in this article. Results: The multipronged strategies including aggressive JE immunization, active surveillance programmes, vector control interventions, case management system, strengthening of health infrastructure at peripheral level, provision for sanitation facilities and safe drinking water, rehabilitation centers for disables, behavior change programmes and nutrition improvement programmes developed by central and state Government helped in significant reduction of AES associated mortality in UP. Conclusion: Uttar Pradesh is now approaching towards finishing one of their ever-challenging chapters of Acute Encephalitis Syndrome outbreaks of last four decades highlighting the success of the multipronged strategies and unwavering commitments made to control and prevent seasonal AES outbreaks in UP.